Airbnb and neighbourhoods: an exploratory study - Petruzzi, Marina A. (2021)
Purpose This study aims to identify residents' perceptions of the impacts of Airbnb through an exploratory study that accounts for 94 residents in Lisbon, Portugal, in neighbourhoods with a high number of accommodations listed on the Airbnb platform. Design/methodology/approach A quantitative research was conducted. A questionnaire was designed and administered within the selected neighbourhoods. Factor analysis using the principal component methods is used to reduce the items evaluated. Findings The study reveals that residents have perceptions of both agreement and disagreement towards the impacts of the sharing economy in economic, environmental and sociocultural aspects. Positively perceived impacts refer to interactions with tourists, natural preservation and increase in business and job opportunities. Conversely, the growth of rent prices, the increase in noise issues, the change in the local culture and the threat of losing authenticity and traditions are the dimensions that may lead to negatively perceived impacts towards Airbnb. Research limitations/implications In spite of being the largest network for sharing accommodation, Airbnb is not the only one. Research on individual perceptions analyses the understandings of each person, which can be built and shaped by the context. In spite of the potential of the Likert scale, qualitative research should be added to enrich future studies. Practical implications This study identified several challenges for Airbnb and other sharing platforms, including residents' concerns over noise, the threat of losing identity, changes in the local culture and rise in rent prices. Originality/value The study is dedicated to analyzing the host community residents and identifying their perceptions of impacts of the sharing economy. The use of residents' perceptions provides useful insights that may be considered when planning, developing and implementing local policies.